1988
DOI: 10.1002/path.1711540210
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of lipid accumulation in the gallbladder mucosa of the ground squirrel fed a lithogenic diet

Abstract: Richardson's ground squirrels (Spermophilus richardsonii) of both sexes were fed a 2 per cent cholesterol-enriched diet for intervals of 12, 18, and 24 h; 3, 5, and 7 days; and 2, 3, 10, and 20 weeks. It was shown that free (unesterified) cholesterol, phospholipid, and cholesterol ester accumulated in specific regions of the gallbladder mucosa during cholelithiasis. Electron microscopy revealed the presence of lipids inter- and intracellularly as early as 12 h after ingestion. By 7 days, lipids were seen in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Research efforts have recently focused on animal models for inducing cholelithiasis by using 0 1989 ALAN R. LISS, INC. the ground squirrel (MacPherson et al, 19871, hamster (Bergman and van der Linden, 1966;Bergman et al, 1968;Dam and Christensen, 1954;Christensen and Dam, 1954;Sondergaard et al, 19691, mouse (Lee and Scott, 19821, prairie dog (Lee et al, 19811, and rabbit (Borgman and Haselden, 1969;Lee et al, 1986). MacPherson et al (1987) and Pemsingh et al (1988) demonstrated that the mucosal epithelium of the gallbladder was able to secrete mucoid compounds which could be the initiators in the cholesterol nucleating process, as was suggested by LaMont and collaborators (1984).…”
Section: Introductionmentioning
confidence: 85%
“…Research efforts have recently focused on animal models for inducing cholelithiasis by using 0 1989 ALAN R. LISS, INC. the ground squirrel (MacPherson et al, 19871, hamster (Bergman and van der Linden, 1966;Bergman et al, 1968;Dam and Christensen, 1954;Christensen and Dam, 1954;Sondergaard et al, 19691, mouse (Lee and Scott, 19821, prairie dog (Lee et al, 19811, and rabbit (Borgman and Haselden, 1969;Lee et al, 1986). MacPherson et al (1987) and Pemsingh et al (1988) demonstrated that the mucosal epithelium of the gallbladder was able to secrete mucoid compounds which could be the initiators in the cholesterol nucleating process, as was suggested by LaMont and collaborators (1984).…”
Section: Introductionmentioning
confidence: 85%
“…Animal models such as the mouse (Caldwell et al, 1965;Hayward, 1962a;Laitio and Terho, 1975;Lee, 1980;Lee and Scott, 1982;Luciano, 1972;Luciano et al, 1973;Trotman et al, 1982;Wahlin, 1976Wahlin, , 1977Ziegler et al, 1982), gerbil (Wahlin, 1979) ground squirrel Pemsingh et al, 1988), guinea pig (Brotschi et al, 1984;Geleff and Böck, 1984;Hayward, 1962b;Wahlin and Schiebler, 1975;etc. ), prairie dog (Haley-Russell et al, 1989;LaMont et al, 1984;Moody et al, 1989), rabbit (Borgman and Haselden, 1969;Lee et al, 1986), and Syrian hamster (Christensen and Dam, 1954;Dam, 1971;Gilloteaux et al, 1992Gilloteaux et al, , 1993a have been used in the study of gallstone formation.…”
Section: Gallstonesmentioning
confidence: 97%
“…In these cells, PPAR-α activation inhibits the increase in tumor necrosis factor (TNF)-α expression triggered by LPS [19]. Activation of PPAR-α also results in the expression of the cholesterol extruder, ABCA1, while the accumulation of cholesterol in biliary epithelial cells is known to elicit inflammation [20]. These observations suggest that PPAR-α activation protects biliary epithelial cells from excessive inflammation.…”
Section: The Role Of Nuclear Receptors In Biliary Epithelium Protectionmentioning
confidence: 99%